Evaluating the usefulness of plasma chromogranin A measurement in cyclic ACTH-dependent Cushing’s syndrome - Keisuke Kakizawa; Miho Yamashita; Yuto Kawauchi; Akira Ikeya; Kenji Ohba; Akio Matsushita (Endocrine Journal)
Cushing’s syndrome, a clinical condition characterized by hypercortisolemia, exhibits distinct clinical signs and is associated with cyclic cortisol secretion in some patients. The clinical presentation of cyclic Cushing’s syndrome can be ambiguous and its diagnosis is often challenging. We experienced a 72-year-old woman with cyclic ACTH-dependent Cushing’s syndrome caused by a pulmonary carcinoid tumor. Diagnosis was challenging because of the extended trough periods, and the responsible lesion was initially unidentified. A subsequent follow-up computed tomography revealed a pulmonary lesion, and ectopic ACTH secretion from this lesion was confirmed by pulmonary artery sampling. Despite the short peak secretion period of ACTH (approximately one week), immunostaining of the surgically removed tumor confirmed ACTH positivity. Interestingly, stored plasma chromogranin A levels were elevated during both peak and trough periods. The experience in evaluating this patient prompted us to investigate the potential use of plasma chromogranin A as a diagnostic marker of ACTH-dependent Cushing’s syndrome. A retrospective study was conducted to determine the efficacy of plasma chromogranin A in three patients with ectopic ACTH syndrome (EAS), including the present case, and six patients with Cushing’s disease (CD) who visited our hospital between 2018 and 2021. Notably, plasma chromogranin A levels were higher in patients with EAS than in those with CD. Additionally, a chromogranin A level in the present case during the trough phase was lower than that in the peak phase, and was similar to those in CD patients. The measurement of plasma chromogranin A levels could aid in differentiating EAS from CD.